2011
DOI: 10.1182/blood-2010-07-296749
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Nef regulatory protein of HIV-1 by a single-domain antibody

Abstract: IntroductionThe advent of monoclonal antibodies was a major breakthrough for the development of antibody-based therapies against various diseases, including virus infection. 1 However, expression in the cytoplasm or nucleus of eukaryotic cells of full-length immunoglobulin G or single-chain antibody variable domain fragments aiming at blocking an intracellular target is poorly efficient because of the reducing nature of these compartments. The engineering of single-chain antibody variable domain fragments (scF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 54 publications
9
65
0
1
Order By: Relevance
“…All other Nef SF2 variants, including 2 Nef variants (AxxA and VGF→AAA) that impact the interaction of Nef with SH3-binding domains, were not found around podosomes and were unable to modify their size (supplemental Figure 5A-B). When wt-Nef SF2 was coexpressed with antiNef single-domain antibodies (sdAbs) and Neffins C1 and B6, 63,64 we observed that Nef SF2 was delocalized from podosomes (data not shown), and F-actin content in podosomes was significantly decreased (supplemental Figure 5C). Neffins C1 and B6 are anti-Nef sdAbs linked to the SH3 domain of the Src family member Hck, which inhibit most Nef biological activities.…”
Section: Hiv-1 Effects On Podosomes and Macrophage Migration Are Medimentioning
confidence: 97%
See 1 more Smart Citation
“…All other Nef SF2 variants, including 2 Nef variants (AxxA and VGF→AAA) that impact the interaction of Nef with SH3-binding domains, were not found around podosomes and were unable to modify their size (supplemental Figure 5A-B). When wt-Nef SF2 was coexpressed with antiNef single-domain antibodies (sdAbs) and Neffins C1 and B6, 63,64 we observed that Nef SF2 was delocalized from podosomes (data not shown), and F-actin content in podosomes was significantly decreased (supplemental Figure 5C). Neffins C1 and B6 are anti-Nef sdAbs linked to the SH3 domain of the Src family member Hck, which inhibit most Nef biological activities.…”
Section: Hiv-1 Effects On Podosomes and Macrophage Migration Are Medimentioning
confidence: 97%
“…Neffins C1 and B6 are anti-Nef sdAbs linked to the SH3 domain of the Src family member Hck, which inhibit most Nef biological activities. 63,64 The strong inhibitory effect of Neffins on podosome size, together with the effects of Nef mutants AxxA and VGF→AAA, suggested a pivotal role of the Nef-SH3 interaction in podosome modulation. In addition, Nef SF2 AxxA failed to increase the life span of podosomes compared with wt-Nef SF2 (supplemental Figure 5D).…”
Section: Hiv-1 Effects On Podosomes and Macrophage Migration Are Medimentioning
confidence: 99%
“…ADCC antibodies within HIV-1 ϩ sera primarily recognize CD4-induced Env epitopes concealed as a result of Vpu-and Nef-mediated CD4-downregulation (23). The inhibition of Nef and Vpu might be a possible strategy to increase recognition of Env-expressing cells (49). On a similar note, we show here that CD4mc have potential therapeutic utility because they can efficiently induce the CD4-bound conformation and increase binding of HIV-1 ϩ serum antibodies to ex vivo-expanded primary CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…293T cells were seeded into T75 flasks at a density of 4 ϫ 10 6 cells and transfected 24 h later with 10 g of the GFP-tagged murine or human UNG2 expression plasmid in combination with the HA-Vpr expression plasmid. After 24 h, the cells were lysed in NP-40 lysis buffer supplemented with protease inhibitor (Roche) for 30 min under gentle agitation at 4°C, as described previously (7). After centrifugation at 13,200 rpm, immunoprecipitations were carried out on 450 g of cell lysate proteins by incubation with 3 g of anti-GFP antibody (7.1/13.1; Roche) and 30 l of protein A-Sepharose 4B beads (Sigma) for 2 h under gentle agitation at 4°C.…”
Section: Methodsmentioning
confidence: 99%